2018
DOI: 10.1038/s41598-018-20096-8
|View full text |Cite
|
Sign up to set email alerts
|

Activated Biomass-derived Graphene-based Carbons for Supercapacitors with High Energy and Power Density

Abstract: Here, we present a facile and low-cost method to produce hierarchically porous graphene-based carbons from a biomass source. Three-dimensional (3D) graphene-based carbons were produced through continuous sequential steps such as the formation and transformation of glucose-based polymers into 3D foam-like structures and their subsequent carbonization to form the corresponding macroporous carbons with thin graphene-based carbon walls of macropores and intersectional carbon skeletons. Physical and chemical activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 39 publications
0
67
0
Order By: Relevance
“…For example, by pre‐carbonization at 900°C and then activation, the prepared CAs have an SSA of 997 m 2 /g, while by pre‐carbonization at 500°C and then activation, the SSA of the prepared CAs is increased by 47% to 1468 m 2 /g . In addition, high temperature can promote the etching of activating agent, improving not only the graphitic degrees but also the SSA and pore structure of carbon materials as mentioned earlier …”
Section: Preparation Methods Of Carbon‐based Materialsmentioning
confidence: 77%
See 4 more Smart Citations
“…For example, by pre‐carbonization at 900°C and then activation, the prepared CAs have an SSA of 997 m 2 /g, while by pre‐carbonization at 500°C and then activation, the SSA of the prepared CAs is increased by 47% to 1468 m 2 /g . In addition, high temperature can promote the etching of activating agent, improving not only the graphitic degrees but also the SSA and pore structure of carbon materials as mentioned earlier …”
Section: Preparation Methods Of Carbon‐based Materialsmentioning
confidence: 77%
“…Besides, good conductivity can also offer a low resistant pathway for electron transfer. This means that porous carbons with graphitic structure are superior to amorphous carbons as electrodes in DLECs . Gabhi et al found that the electrical conductivity of biochar was highly dependent on its degree of graphitization.…”
Section: Biomass‐based Carbon For Electrode Materialsmentioning
confidence: 99%
See 3 more Smart Citations